Enhancing Nationally Determined Contribution (NDC) ambition for soil organic carbon protection and sequestration - Wiese-Rozanova, Liesl D.; Alcántara Shivapatham, Viridiana; Wollenberg, Eva Karoline (2019)
An estimated 18 to 37 billion tons of carbon could be sequestered in croplands globally over the next 20 years by implementing best practices for soil organic carbon (SOC) sequestration (Zomer et al. 2017). In addition, more than 380 billion tons of carbon are at risk of loss from carbon dense peatlands in the top 20 countries with the largest peatland stocks alone (Crump 2017). SOC protection and sequestration are therefore major greenhouse gas (GHG) mitigation options, especially to contribute to the negative emissions needed to achieve the 2050 global policy targets. Increasing SOC levels can also provide substantial additional benefits for adaptation, food security and biodiversity, including nutrient cycling and water availability.